“Improving the existing public sector strategic planning guidelines towards integrated provincial and local government strategic planning processes : lessons learned from Eastern Cape" - Maxegwana, Malusi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2012.